Open Office Space: The Wave of the Future for Academic Health Centers?. (January 2020) - Barnes, Janice; Wineman, Jean; Adler, Nancy
Abstract : Facing space constraints similar to those experienced by many urban campuses, the University of California, San Francisco (UCSF) looked to innovative office workplace design to curb growing facilities expenditures. Mission Hall, a new office building primarily for desktop and clinical researchers and staff, was designed as an activity-based workplace (ABW), a type of open-space design. ABW was simultaneously being proposed as the template for future UCSF desktop research workspaces. ABWs can be less costly to construct than other designs, and their mix of shared and open workspaces is intended to improve efficiency and interaction. Evaluations of ABWs in corporate settings have yielded mixed results. Examples of ABW buildings for faculty in academic health centers (AHCs) are rare. The Mission Hall experience provided a unique opportunity to understand the impact of an ABW design on faculty satisfaction, work effectiveness, well-being, and engagement. In a 2016 survey of faculty, 1 year after occupancy, respondents reported adverse changes in all 4 areas. The most common complaints involved noise exposure and lack of visual and auditory privacy. In response to these issues, faculty reported working at home or elsewhere more frequently, making collaboration more difficult. In 2018, UCSF retrofitted the building to create some private offices and adjusted its overall program to balance private office and open workspaces in future projects. Lessons drawn from this experience can inform workplace solutions at other AHCs. Most critical are the needs to assess functional requirements of work and align design, change management, and technologies to support those requirements. Abstract : Supplemental Digital Content is available in the text.